CATALYST LAYER, MEMBRANE ELECTRODE ASSEMBLY FOR SOLID POLYMER ELECTRODE FUEL CELL, AND SOLID POLYMER ELECTRODE FUEL CELL
Patent Information
- Application Number
- JP2021567411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-12-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-12-18
AI Technical Summary
【0008】 本開示によれば、固体高分子形燃料電池に用いることで触媒使用量を削減しつつ燃料電池の高出力化が実現される触媒層、前記触媒層を用いた固体高分子形燃料電池用膜電極接合体、及び前記固体高分子形燃料電池用膜電極接合体を備えた固体高分子形燃料電池を提供できる。
Smart Images

Figure 0007643347000008 
Figure 0007643347000001 
Figure 0007643347000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a catalyst layer, a membrane electrode assembly for a polymer electrolyte fuel cell, and a polymer electrolyte fuel cell. [Background technology]
[0002] A polymer electrolyte fuel cell is, for example, a cell formed by sandwiching a membrane electrode assembly between two separators, and a plurality of such cells are stacked. The membrane electrode assembly includes, for example, an anode having a catalyst layer and a gas diffusion layer, a cathode having a catalyst layer and a gas diffusion layer, and a polymer electrolyte membrane disposed between the anode and the cathode.
[0003] The catalyst layers used in the anode and cathode are configured to include, for example, a catalyst support in which a catalyst is supported on a support, and an ionomer which is a polymer electrolyte. Since platinum, which is mainly used as a catalyst, is expensive, it is desirable to reduce the amount of catalyst used. Therefore, in order to utilize the catalyst efficiently, attempts have been made to increase the output of fuel cells while reducing the amount of catalyst used by coating as many catalyst particles as uniformly as possible with ionomer (for example, Patent Documents 1 to 3, etc.).
[0004] Patent Document 1: JP 2010-167379 A Patent Document 2: JP 2010-186678 A Patent Document 3: JP 2011-081977 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, in order to simultaneously reduce the amount of catalyst used and increase the output of fuel cells, it has been conventionally believed that it is necessary to coat as many catalyst particles as uniformly as possible with ionomer in order to form a wide three-phase interface between the catalyst, ionomer, and water, which is the reaction field in the catalyst layer. However, when a platinum-containing catalyst is used as the catalyst, there is a demand for a fuel cell that can achieve a higher output while reducing the amount of catalyst used.
[0006] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a catalyst layer that, when used in a polymer electrolyte fuel cell, enables the fuel cell to achieve high output while reducing the amount of catalyst used, a membrane electrode assembly for a polymer electrolyte fuel cell using the catalyst layer, and a polymer electrolyte fuel cell including the membrane electrode assembly for a polymer electrolyte fuel cell. [Means for solving the problem]
[0007] Specific means for achieving the above object are as follows. <1> The catalyst layer includes a catalyst-supported carbon in which a platinum-containing catalyst is supported on a carbon support, and an ionomer, The catalyst-supporting carbon has mesopores with a pore diameter of 2 nm or more and less than 10 nm in a pore distribution obtained by a nitrogen adsorption method, At least a portion of the ionomer is present in the mesopores having a pore diameter of 2 nm or more and less than 10 nm, The content of the ionomer relative to 100 parts by mass of the carbon support is 100 parts by mass or more, The catalyst layer has a ratio of the ionomer to the total volume of the mesopores having a pore diameter of 2 nm or more and less than 10 nm of 50 vol % or less. <2> The catalyst-supporting carbon in the catalyst layer, with the ionomer attached, has a pore distribution obtained by a nitrogen adsorption method that has a pore diameter of 50 nm or more of 0.03 cm 3 / g or more catalyst <1> The catalyst layer according to claim 1. <3> The content of the catalyst per unit area of the catalyst layer is 0.2 mg / cm 2 is less than or equal to <1> or <2> The catalyst layer according to claim 1. <4> The catalyst includes at least one selected from the group consisting of platinum particles and platinum alloy particles. <1> ~ <3> 13. The catalyst layer according to claim 12 . <5> The number average particle size of the catalyst is 1 nm to 20 nm. <4> The catalyst layer according to claim 1. <6> The content of the catalyst relative to the total catalyst-supporting carbon is 10% by mass to 70% by mass. <1> ~ <5> 13. The catalyst layer according to claim 12 . <7> an anode having a first gas diffusion layer and a first catalyst layer provided on one surface of the first gas diffusion layer; a cathode having a second gas diffusion layer and a second catalyst layer provided on one surface of the second gas diffusion layer; a polymer electrolyte membrane disposed between the first catalyst layer and the second catalyst layer; Equipped with At least one of the first catalyst layer and the second catalyst layer is <1> ~ <6> 2. A membrane electrode assembly for a polymer electrolyte fuel cell, comprising the catalyst layer according to claim 1. <8> <7> A solid polymer electrolyte fuel cell comprising the membrane electrode assembly for a solid polymer electrolyte fuel cell according to claim 1. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a catalyst layer that can be used in a polymer electrolyte fuel cell to reduce the amount of catalyst used while increasing the output of the fuel cell, a membrane electrode assembly for a polymer electrolyte fuel cell using the catalyst layer, and a polymer electrolyte fuel cell including the membrane electrode assembly for a polymer electrolyte fuel cell. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a membrane electrode assembly for a polymer electrolyte fuel cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments for carrying out the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values and their ranges, and do not limit the present disclosure.
[0011] In this specification, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In this specification, the numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the present specification, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. When an embodiment is described with reference to the drawings in this specification, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.
[0012] [Catalyst layer] The catalyst layer in this embodiment is a catalyst layer containing a catalyst-supporting carbon in which a platinum-containing catalyst is supported on a carbon support, and an ionomer. Mesopores generally mean pores with a pore diameter of 2 nm or more and less than 50 nm, but in this embodiment, an ionomer occupies a specific proportion of the volume in mesopores with a pore diameter of 2 nm or more and less than 10 nm. That is, the catalyst-supporting carbon has mesopores with a pore diameter of 2 nm or more and less than 10 nm in a pore distribution obtained by a nitrogen adsorption method, at least a part of the ionomer is present in the mesopores with a pore diameter of 2 nm or more and less than 10 nm, the content of the ionomer is 100 parts by mass or more relative to 100 parts by mass of the carbon support, and the occupancy rate of the ionomer in the total volume of the mesopores with a pore diameter of 2 nm or more and less than 10 nm is 50 volume % or less.
[0013] Hereinafter, the pore distribution obtained by the nitrogen adsorption method is simply referred to as "pore distribution", pores having a diameter of 2 nm or more and less than 50 nm are also referred to as "mesopores", mesopores having a pore diameter of 2 nm or more and less than 10 nm in the pore distribution are also referred to as "specific mesopores", and the ionomer occupancy rate in the total volume of specific mesopores is also referred to as "ionomer occupancy rate". In addition, "macropores" described later refer to pores having a pore diameter of 50 nm or more and less than 300 nm. The "pore distribution" is obtained by analyzing the sample to be measured by the BJH method using an automatic specific surface area / pore distribution measuring device (e.g., Shimadzu Corporation, model number: Tristar II 3020, measurement method: nitrogen adsorption method by constant volume method). The specific surface area and pore volume of the catalyst-supporting carbon described later are calculated from the pore distribution.
[0014] The above "ionomer occupancy" is a value represented by the following formula (1), where P1 is the total volume of specific mesopores obtained by performing the above measurements and analyses on a sample of catalyst-supported carbon to which an ionomer has been attached, and P0 is the total volume of specific mesopores obtained by performing the above measurements and analyses on a sample of catalyst-supported carbon to which no ionomer has been attached. The total volume of specific mesopores means the total pore area of the specific mesopores. Ionomer occupancy (volume%) = (P0-P1) × 100 / P0 (1)
[0015] As a sample of the catalyst-supported carbon to which the ionomer is attached, for example, a coating liquid for forming a catalyst layer is applied onto a substrate film such as a PET film, and the coating layer is formed by drying at 80°C to remove the solvent, and the obtained coating layer is scraped off to obtain a powder. As a sample of the catalyst-supported carbon to which the ionomer is not attached, for example, a mixture of the catalyst-supported carbon and a solvent is applied to a substrate film such as a PET film, dried to remove the solvent to form a coating layer, and the resulting coating layer is scraped off to obtain a powder. Here, the above-mentioned "PET" means polyethylene terephthalate. It is preferable that the above-mentioned mixture is subjected to the same mixing process (e.g., mixing process using a bead mill) as that performed in the process of preparing the coating liquid for forming the catalyst layer.
[0016] The catalyst layer described above can be used in a polymer electrolyte fuel cell to reduce the amount of catalyst used while increasing the output of the fuel cell. The reason for this is unclear, but is presumed to be as follows. The specific mesopores have a large pore surface area relative to the pore volume. Therefore, the surface area of a carbon support having the specific mesopores becomes very large. For example, even in a carbon support in which the ratio of the total pore volume of the specific mesopores to the total pore volume of all mesopores and macropores in the carbon support is about 30%, the ratio of the total pore surface area of the specific mesopores to the total pore surface area of all mesopores and macropores in the carbon support may exceed 85%. In other words, in a catalyst-supported carbon in which particles of a catalyst containing platinum are supported on the surface of a carbon support, although there are catalysts supported on surfaces other than the pores or on the surfaces of the macropores in the carbon support, most of the catalyst is considered to be supported on the surfaces of the specific mesopores.
[0017] Therefore, in order to bring the ionomer into contact with as much catalyst as possible, attempts have been made to allow the ionomer to enter the inside of the pores, thereby bringing the catalyst and the ionomer into contact with each other inside the pores. However, it has become clear that when an ionomer comes into contact with platinum catalyst particles, it can be poisoned by the acidic functional groups of the ionomer, and the catalytic activity of the platinum can actually decrease.
[0018] Therefore, in the catalyst layer of this embodiment, the content of the ionomer relative to 100 parts by mass of the carbon support is 100 parts by mass or more, and at least a part of the ionomer is present in the specific mesopores with an ionomer occupancy rate of 50% by volume or less. In the catalyst layer of this embodiment, the catalyst-supported carbon is surrounded by a sufficient amount of ionomer, while the amount of ionomer that enters the specific mesopores is small. The ionomer that surrounds the catalyst-supported carbon but does not enter the specific mesopores is in a state of being close to the catalyst supported in the specific mesopores without contacting them. It is considered that the ionomer in a state of being close to the catalyst without contacting it forms a pseudo three-phase interface through water in the reaction gas (e.g., hydrogen, oxygen, etc. used in the operation of the cell) or water generated by the reaction. It is considered that the catalytic activity of platinum can be effectively utilized by forming a pseudo three-phase interface while suppressing the decrease in catalytic activity of platinum due to the ionomer directly contacting platinum. For the reasons described above, it is believed that the catalyst layer of this embodiment realizes high output of a fuel cell while reducing the amount of catalyst used. Each component constituting the catalyst layer will be described below.
[0019] <Catalyst-supported carbon> The catalyst-supporting carbon has a carbon support having specific mesopores and a catalyst containing platinum supported on the carbon support. The carbon support and the catalyst will be described below.
[0020] The carbon support is not particularly limited as long as it is carbon having at least the specific mesopores. Examples of the carbon support include activated carbon and carbon black, and from the viewpoint of high chemical durability, those at least partially graphitized by heat treatment or the like are preferred. From the viewpoint of keeping the ionomer occupancy low, the carbon support is preferably mesoporous carbon in which the ratio of the total pore volume occupied by macropores is less than 40% of the total pore volume of the mesopores and macropores as a whole. The ratio of the total pore volume occupied by macropores is preferably 5 to 35%, more preferably 10 to 30%.
[0021] The catalyst is not particularly limited as long as it contains platinum and promotes the oxidation-reduction reaction in the polymer electrolyte fuel cell. The catalyst is preferably at least one selected from the group consisting of platinum and platinum alloys, and more preferably contains at least one selected from the group consisting of platinum particles and platinum alloy particles. The platinum alloy is preferably an alloy of platinum and one or more metals selected from the group consisting of platinum group metals other than platinum (ruthenium, rhodium, palladium, osmium, iridium), gold, silver, chromium, iron, titanium, manganese, cobalt, nickel, molybdenum, tungsten, aluminum, silicon, zinc, and tin. The platinum alloy may contain an intermetallic compound of platinum and a metal that is alloyed with platinum.
[0022] When the catalyst contains at least one selected from the group consisting of platinum particles and platinum alloy particles, the number average particle diameter of the catalyst is, for example, in the range of 1 nm to 20 nm, and from the viewpoints of power generation performance and catalyst durability, is preferably in the range of 2 nm to 10 nm, and more preferably in the range of 2 nm to 7 nm. The number-average particle diameter of the catalyst is a value obtained by taking the number-average of the circle-equivalent diameters of 300 to 400 particles in an image observed at 300,000 magnification using a transmission electron microscope (TEM) HT7700 manufactured by Hitachi High-Technologies Corporation.
[0023] The method for supporting the catalyst on the carbon support is not particularly limited, and known methods such as sputtering, solution method, electrolytic deposition, and electroless plating can be used.
[0024] The catalyst content relative to the total catalyst-supporting carbon is, for example, in the range of 10% by mass to 70% by mass. From the viewpoint of achieving both a reduction in the amount of catalyst used and an increase in output, the range of 20% to 60% is preferable, and the range of 30% to 60% is more preferable. The catalyst content per unit area of the catalyst layer is 0.01 mg / cm, which is the optimal thickness for efficient electrode reaction. 2 ~0.50mg / cm 2 is preferable, and from the viewpoint of the balance between the cost of the raw material and the performance, 0.05 mg / cm 2 ~0.35mg / cm 2 In particular, in the catalyst layer of the present embodiment, since high output can be achieved while reducing the amount of catalyst used, the catalyst content per unit area of the catalyst layer is preferably 0.20 mg / cm. 2 It may be the following.
[0025] The specific surface area of the entire catalyst-supporting carbon is set to, for example, 200 m from the viewpoint of achieving both a reduction in the amount of catalyst used and high output. 2 / g catalyst or more is preferable, and 250m 2 The specific surface area of the catalyst-supporting carbon as a whole means the total surface area of the catalyst-supporting carbon per unit mass in a state where no ionomer is attached. The specific surface area of the entire catalyst-supporting carbon is 700 m 2 / g catalyst or less, 2 / g catalyst or less, 350m 2 / g catalyst or less. The specific surface area of the entire catalyst-supporting carbon is measured by nitrogen adsorption onto the carbon surface using a BET specific surface area device.
[0026] The specific surface area of the mesopores in the catalyst-supported carbon is, for example, 200 m2 in order to achieve both a reduction in the amount of catalyst used and high output. 2 / g catalyst or more is preferable, and 250m 2The specific surface area of the mesopores in the catalyst-supporting carbon is the total pore surface area of the mesopores in the catalyst-supporting carbon per unit mass in a state where no ionomer is attached. The specific surface area of the entire catalyst-supporting carbon is preferably in the range of 700 m 2 / g catalyst or less, 2 / g catalyst or less, 350m 2 / g catalyst or less.
[0027] The specific surface area of the specific mesopores in the catalyst-supported carbon is, for example, 200 m2 from the viewpoint of achieving both a reduction in the amount of catalyst used and high output. 2 The specific surface area of the specific mesopores in the catalyst-supporting carbon means the total pore surface area of the specific mesopores in the catalyst-supporting carbon per unit mass in a state where no ionomer is attached.
[0028] The total pore volume of a specific mesopore in a catalyst-supported carbon per unit mass without ionomer attachment is, for example, 0.1 cm 3 / g catalyst~0.8cm 3 From the viewpoint of gas diffusion and power generation performance, the range of 0.15 cm 3 / g catalyst~0.7cm 3 / g catalyst range is preferred, with 0.2 cm 3 / g catalyst ~ 0.6cm 3 / g catalyst range is more preferred. The proportion of the total pore volume of specific mesopores in the total pore volume of all mesopores and macropores in the catalyst-supporting carbon without ionomer attachment is, for example, in the range of 20% to 90%, and from the viewpoints of drainage of generated water and power generation performance, is preferably in the range of 25% to 80%, and more preferably in the range of 30% to 70%.
[0029] The total pore volume of macropores in the catalyst-supported carbon per unit mass without ionomer attachment is, for example, 0.05 cm 3 From the viewpoint of achieving both a reduction in catalyst usage and high output, a range of 0.07 cm3 / g catalyst~0.50cm 3 / g catalyst range is preferred, with 0.1 cm 3 / g catalyst~0.4cm 3 / g catalyst range is more preferred.
[0030] <Ionomer> The ionomer is not particularly limited as long as it is a polymer compound having an ion exchange group, and among them, a polymer compound having proton conductivity is preferable. Hereinafter, a polymer compound having an ion exchange group is also referred to as an "ion exchange resin". "Ion exchange group" means H + , a group having a monovalent metal cation, an ammonium ion, or the like. Examples of the ion exchange group include a sulfonic acid group, a sulfonimide group, a sulfonamide group, a sulfonmethide group, a carboxyl group, and a phosphate group, and among these, a sulfonic acid group having excellent proton conductivity is preferred. The ion exchange group may be used alone or in combination of two or more kinds.
[0031] As the ionomer, from the viewpoint of durability, a fluorine-containing ion exchange resin is preferable, and a perfluorocarbon polymer having an ion exchange group is more preferable. The perfluorocarbon polymer may contain an etheric oxygen atom. Examples of the perfluorocarbon polymer include known polymers such as polymer (H) described below, polymer (Q) described below, and polymers having a structural unit derived from a perfluoromonomer having an ion exchange group and a 5-membered ring, as described in International Publication No. 2011 / 013577, etc. In terms of availability and ease of production, the ionomer preferably contains at least one selected from the group consisting of polymer (H) and polymer (Q).
[0032] The term "polymer" refers to a compound having a structure composed of multiple structural units. The term "structural unit" refers to a unit derived from a monomer formed by polymerization of the monomer. The structural unit may be a unit formed directly by a polymerization reaction of a monomer, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer. The term "monomer" refers to a compound having a polymerizable carbon-carbon double bond.
[0033] Polymer (H): The polymer (H) is a polymer having the following unit (U1) (excluding the polymer (Q)).
[0034] [ka]
[0035] However, in the above unit (U1), Q 3 is a single bond or a perfluoroalkylene group which may have an ethereal oxygen atom, R f2 is a perfluoroalkyl group which may have an ether oxygen atom, and X 2 is an oxygen atom, a nitrogen atom, or a carbon atom; b is X 2 is 0 for oxygen atoms, and X 2 is 1 for nitrogen atom, and X 2 is 2 for carbon atoms, and Y 2 is a fluorine atom or a monovalent perfluoro organic group, and t is 0 or 1. A single bond is 2 and the sulfur atom of SO2 are directly bonded. An organic group refers to a group containing one or more carbon atoms.
[0036] Q in the above unit (U1) 3When the perfluoroalkylene group represented by the formula (I) has an etheric oxygen atom, the number of the oxygen atoms may be one or more. In addition, the oxygen atom may be inserted between the carbon atom-carbon atom bond of the perfluoroalkylene group, or may be inserted at the carbon atom bond terminal. The perfluoroalkylene group may be linear or branched. The perfluoroalkylene group preferably has 1 to 6 carbon atoms, and more preferably has 1 to 4 carbon atoms.
[0037] R in the above unit (U1) f2 The perfluoroalkyl group represented by the formula (I) may be linear or branched, and is preferably linear. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 6, and more preferably 1 to 4. As the perfluoroalkyl group, a perfluoromethyl group, a perfluoroethyl group, and the like are preferable.
[0038] In the above unit (U1), -(SO2X 2 (SO2R f2 ) b ) - H + The group is an ion exchange group. -(SO2X 2 (SO2R f2 ) b ) - H + The group is a sulfonic acid group (-SO3 - H + group), sulfonimide group (-SO2N(SO2R f2 ) - H + group), or sulfonmethide group (-SO2C(SO2R f2 )2) - H + Groups such as Y in the above unit (U1) 2 is preferably a fluorine atom or a trifluoromethyl group.
[0039] As the unit (U1), the following unit (U1-1) is preferable, and the following unit (U1-11), unit (U1-12), unit (U1-13), or unit (U1-14) is more preferable in terms of ease of production of the polymer (H) and ease of industrial implementation.
[0040] [ka]
[0041] In the above unit (U1-1), Z is a fluorine atom or a trifluoromethyl group, t is 0 or 1, m is an integer of 0 to 3, n is an integer of 1 to 12, p is 0 or 1, and m+p>0.
[0042] The polymer (H) may further contain structural units derived from other monomers (hereinafter, referred to as "other units"). The proportion of the other units may be appropriately adjusted so that the ion exchange capacity of the polymer (H) falls within the preferred range described below. As the other units, from the viewpoint of mechanical strength and chemical durability, a constitutional unit derived from a perfluoromonomer is preferable, and a constitutional unit derived from tetrafluoroethylene (hereinafter referred to as TFE) is preferable. The following building blocks are more preferred.
[0043] The polymer (H) can be produced by polymerizing the following compound (M1) and, if necessary, other monomers to obtain a precursor polymer, and then converting the -SO2F groups in the precursor polymer to sulfonic acid groups. The conversion of the -SO2F groups to sulfonic acid groups is carried out by hydrolysis and an acid-form treatment. CF2=CF-(CF2) t OCF2-CFY 2 -Q 3 -SO2F···(M1). In addition, t and Y in the above compound (M1) 2 , and Q 3 are t and Y in the unit (U1), respectively. 2 , and Q 3 is synonymous with.
[0044] Polymer (Q): The polymer (Q) is a polymer having at least one of the following unit (U2) and the following unit (U3).
[0045] [ka]
[0046] However, in the above unit (U2), Q 1 is a perfluoroalkylene group which may have an ether oxygen atom, and Q 2 is a single bond or a perfluoroalkylene group which may have an ethereal oxygen atom, R f1 is a perfluoroalkyl group which may have an ether oxygen atom, and X 1 is an oxygen atom, a nitrogen atom, or a carbon atom; 1 is 0 for oxygen atoms, and X 1 is 1 for nitrogen atom, and X 1 is 2 for carbon atoms, and Y 1 is a fluorine atom or a monovalent perfluoro organic group, and s is 0 or 1. A single bond is represented by CY 1 and the sulfur atom of SO2 are directly bonded. An organic group refers to a group containing one or more carbon atoms.
[0047] In the above unit (U2), Q 1 , Q 2 When the perfluoroalkylene group has an etheric oxygen atom, the number of the oxygen atoms may be one or more. In addition, the oxygen atom may be inserted between the carbon atom-carbon atom bond of the perfluoroalkylene group, or may be inserted at the carbon atom bond terminal. The perfluoroalkylene group may be linear or branched, and is preferably linear. The number of carbon atoms in the perfluoroalkylene group is preferably from 1 to 6, more preferably from 1 to 4. When the number of carbon atoms is 6 or less, the boiling point of the raw material fluorine-containing monomer becomes low, and purification by distillation becomes easy.
[0048] Q in the above unit (U2) 2 is preferably a perfluoroalkylene group having 1 to 6 carbon atoms which may have an etheric oxygen atom. 2 is a perfluoroalkylene group having 1 to 6 carbon atoms which may have an ether oxygen atom, 2 is a single bond, the power generation performance is more stable when the solid polymer electrolyte fuel cell is operated for a long period of time. In the above unit (U2), Q 1 , Q 2 At least one of them is preferably a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom. A fluorine-containing monomer having a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom can be synthesized without going through a fluorination reaction with fluorine gas, and therefore the yield is good and the production is easy.
[0049] In the above unit (U2), R f1 The perfluoroalkyl group may be linear or branched, and is preferably linear. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 6, and more preferably 1 to 4. As the perfluoroalkyl group, a perfluoromethyl group, a perfluoroethyl group, and the like are preferable. R with two or more units (U2) f1 If R f1 may be the same group or different groups.
[0050] In the above unit (U2), -(SO2X 1 (SO2R f1 ) a ) - H + The group is an ion exchange group. -(SO2X 1 (SO2Rf1 ) a ) - H + The group is a sulfonic acid group (-SO3 - H + group), sulfonimide group (-SO2N(SO2R f1 ) - H + group), or sulfonmethide group (-SO2C(SO2R f1 )2) - H + Groups such as Y in the above unit (U2) 1 is preferably a linear perfluoroalkyl group having 1 to 6 carbon atoms which may have a fluorine atom or an ethereal oxygen atom.
[0051] As the unit (U2), the following unit (U2-1) is preferable, and the following unit (U2-11), unit (U2-12), or unit (U2-13) is more preferable in terms of ease of production of the polymer (Q) and ease of industrial implementation.
[0052] [ka]
[0053] However, in the above unit (U2-1), R F11 is a single bond or a linear perfluoroalkylene group having 1 to 6 carbon atoms which may have an etheric oxygen atom, R F12 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, and s is 0 or 1.
[0054] [ka]
[0055] However, in the above unit (U3), R F1 and R F2 each independently represents a perfluoroalkylene group having 1 to 3 carbon atoms. R F1 and RF2 Specific examples include -CF2-, -CF2CF2-, -CF(CF3)-, -CF2CF2CF2-, -CF(CF2CF3)-, -CF(CF3)CF2-, -CF2CF(CF3)-, and -C(CF3)(CF3)-. R is a polymer that is inexpensive, easy to manufacture, and can increase the ion exchange capacity of the polymer (Q). F1 and R F2 are each independently preferably a perfluoroalkylene group having 1 or 2 carbon atoms. When the number of carbon atoms is 2, it is preferably linear. Specifically, -CF2-, -CF2CF2- or -CF(CF3)- is preferred, -CF2- or -CF2CF2- is more preferred, and -CF2- is particularly preferred. As the unit (U3), the following unit (U3-1) is preferable.
[0056] [ka]
[0057] The polymer (Q) may further contain other units. The proportion of the other units may be appropriately adjusted so that the ion exchange capacity of the polymer (Q) falls within the preferred range described below. As the other units, from the viewpoints of mechanical strength and chemical durability, constitutional units derived from perfluoromonomers are preferred, and constitutional units derived from TFE are more preferred.
[0058] Polymer (Q) can be produced, for example, by the methods described in WO 2007 / 013533, WO 2020 / 116651, etc.
[0059] The ion exchange capacity of the ionomer is preferably 0.5 to 2.0 milliequivalents / g dry resin, particularly preferably 0.8 to 1.5 milliequivalents / g dry resin, from the viewpoints of electrical conductivity and gas permeability.
[0060] The content of the ionomer relative to 100 parts by mass of the carbon support is 100 parts by mass or more, and from the viewpoint of achieving both a reduction in the amount of catalyst used and an increase in output, the content is preferably 100 parts by mass to 240 parts by mass, more preferably 110 parts by mass to 200 parts by mass, and even more preferably 120 parts by mass to 180 parts by mass.
[0061] <Characteristics of the catalyst layer> The ionomer occupancy is 50% by volume or less, and from the viewpoint of achieving both a reduction in the amount of catalyst used and high output, it is preferably 10% by volume to 50% by volume. Furthermore, from the viewpoint of achieving both a reduction in the amount of catalyst used and high output in a low humidity environment (for example, an environment with a humidity of 30%), the ionomer occupancy is more preferably 15% by volume to 40% by volume, and further preferably 20% by volume to 35% by volume.
[0062] Examples of a method for increasing the ionomer content while decreasing the ionomer occupancy rate include a method for adjusting the mixing treatment conditions performed in the process of preparing the coating liquid for forming a catalyst layer, a method for adjusting the properties of the material used in preparing the coating liquid for forming a catalyst layer, and the like, and these methods may be used in combination. Methods for adjusting the mixing conditions include reducing the shear stress applied in the mixing process and shortening the mixing time. Methods for adjusting the material properties include the use of thickening ionomers (e.g., ionomers whose viscosity has been increased by adding a fluorine-based solvent), the use of ionomers with large molecular weights, and the use of hydrophilic catalyst-supported carbon (e.g., catalyst-supported carbon whose surface has been treated with an acid to increase the amount of hydrophilic functional groups).
[0063] The catalyst-supported carbon in the catalyst layer has 0.03 cm2 of macropores with a pore diameter of 50 nm or more in the pore distribution obtained by the nitrogen adsorption method with the ionomer attached. 3 It is preferable to have at least 1000 g of catalyst. The total pore volume of macropores per unit mass of the catalyst-supported carbon in the ionomer-attached state is, for example, 0.03 cm 3 / g catalyst~0.3cm 3From the viewpoint of achieving both a reduction in catalyst usage and high output, a range of 0.05 cm 3 / g catalyst~0.25cm 3 / g catalyst range is preferred, with 0.07 cm 3 / g catalyst~0.20cm 3 / g catalyst range is more preferred.
[0064] The thickness of the catalyst layer is not particularly limited, and may be, for example, in the range of 0.5 μm to 10 μm, preferably in the range of 1 μm to 8 μm, and more preferably in the range of 2 μm to 6 μm. The thickness of the catalyst layer is measured by observing the cross section of the catalyst layer with a scanning electron microscope or the like.
[0065] <Method of manufacturing catalyst layer> The method for producing the catalyst layer includes, for example, a preparation step of preparing a coating liquid for forming a catalyst layer, and a catalyst layer formation step of applying the coating liquid for forming a catalyst layer to the surface of a layer (such as a gas diffusion layer or a polymer electrolyte membrane) that comes into contact with the catalyst layer in a membrane electrode assembly or to the surface of a substrate film, and drying the coating liquid to form a catalyst layer. When the coating liquid for forming a catalyst layer is applied to the surface of a substrate film, a transfer step may be further carried out in which the formed catalyst layer is transferred to the surface of a layer that will be in contact with the catalyst layer in a membrane / electrode assembly.
[0066] In the preparation step, for example, a catalyst-supporting carbon, an ionomer, and, if necessary, a solvent are mixed to prepare a coating liquid for forming a catalyst layer. The catalyst-supporting carbon and the ionomer may each be dispersed in a solvent in advance. That is, a dispersion in which the catalyst-supporting carbon is dispersed and a dispersion in which the ionomer is dispersed may be mixed. Examples of the solvent include aqueous solvents such as water, alcohol, and mixtures thereof, and organic solvents. Among these, aqueous solvents are preferred from the viewpoint of safety during coating and drying. The mixing method is not particularly limited, and examples thereof include known mixing methods such as mixing with a bead mill, mixing with a ball mill, mixing with an ultrasonic disperser, and jet mill. Among these, the mixing method with a bead mill is preferred from the viewpoint of reducing the ionomer content. The solid content concentration of the coating liquid for forming a catalyst layer is not particularly limited, and may be, for example, in the range of 5% by mass to 30% by mass.
[0067] The substrate film used in the catalyst layer formation step includes, in addition to PET film, ETFE film, olefin resin film, etc. In addition, the above "ETFE" stands for tetrafluoroethylene-ethylene copolymer resin. The method for applying the coating liquid for forming a catalyst layer is not particularly limited, and examples thereof include known methods such as a die coating method. A known method is used to dry the layer of the coating liquid for forming a catalyst layer. The drying temperature is, for example, in the range of 40° C. to 130° C., and preferably in the range of 45° C. to 80° C. The drying time is, for example, in the range of 0.5 minutes to 10 minutes, and preferably in the range of 1 minute to 7 minutes.
[0068] [Membrane electrode assembly for polymer electrolyte fuel cells] The membrane electrode assembly for a polymer electrolyte fuel cell in this embodiment (hereinafter also referred to as "membrane electrode assembly") comprises an anode having a first gas diffusion layer and a first catalyst layer provided on one side of the first gas diffusion layer, a cathode having a second gas diffusion layer and a second catalyst layer provided on one side of the second gas diffusion layer, and a polymer electrolyte membrane disposed between the first catalyst layer and the second catalyst layer, and at least one of the first catalyst layer and the second catalyst layer is the above-mentioned catalyst layer. Hereinafter, the membrane electrode assembly in this embodiment will be described with reference to the drawings.
[0069] FIG. 1 shows a schematic cross-sectional view of an example of an embodiment of the membrane electrode assembly of the present embodiment, in which the above-mentioned catalyst layer is used as the second catalyst layer, which is the cathode catalyst layer. The membrane electrode assembly 10 shown in FIG. 1 comprises an anode 13 having a catalyst layer 11 and a gas diffusion layer 12, a cathode 14 having a catalyst layer 21 and a gas diffusion layer 22, and a polymer electrolyte membrane 15 disposed between the anode 13 and the cathode 14 in a state of contact with the catalyst layer 11 and the catalyst layer 21. The catalyst layer 21 is the above-mentioned catalyst layer.
[0070] The catalyst layer 21 and the catalyst layer 11 may be layers having the same components, composition, thickness, etc., or may be layers having different components, composition, thickness, etc. The catalyst layer 11 may be, for example, a layer containing catalyst-supported carbon and an ionomer. The catalyst layer 11 may be the catalyst layer according to the above-mentioned embodiment, or may be a catalyst layer other than the catalyst layer according to the above-mentioned embodiment. The catalyst-supported carbon and the ionomer in the catalyst layer 11 may be the same as those in the catalyst layer according to the above-mentioned embodiment.
[0071] The gas diffusion layer 12 and the gas diffusion layer 22 have a function of uniformly diffusing gas in the catalyst layer 11 and the catalyst layer 21, respectively, and a function as a current collector. The gas diffusion layer 12 and the gas diffusion layer 22 are made of, for example, a gas diffusing substrate. Examples of the gas diffusion layer 12 and the gas diffusion layer 22 include carbon paper, carbon cloth, and carbon felt. The gas diffusion layer 12 and the gas diffusion layer 22 are preferably treated to be water repellent with polytetrafluoroethylene or the like. The gas diffusion layer 12 and the gas diffusion layer 22 may be layers having the same components, composition, thickness, and the like, or may be layers having different components, composition, thickness, and the like.
[0072] The anode 13 may have a carbon layer (not shown) as an intermediate layer between the catalyst layer 11 and the gas diffusion layer 12. Similarly, the cathode 14 may have a carbon layer (not shown) as an intermediate layer between the catalyst layer 21 and the gas diffusion layer 22. By having the carbon layer, the gas diffusibility on the surface of the catalyst layer is improved, and the power generation performance of the solid polymer fuel cell is greatly improved. The carbon layer may be, for example, a layer containing carbon and a non-ionic fluorine-containing polymer. The carbon used in the carbon layer may be, for example, a carbon nanofiber having a fiber diameter of 1 nm to 1000 nm and a fiber length of 1000 μm or less. The non-ionic fluorine-containing polymer may be, for example, polytetrafluoroethylene.
[0073] The polymer electrolyte membrane 15 is a membrane containing an ion exchange resin. As the ion exchange resin, from the viewpoint of durability, a fluorine-containing ion exchange resin is preferable, a perfluorocarbon polymer having an ion exchange group is more preferable, the above-mentioned polymer (H) or polymer (Q) is further preferable, and polymer (H) is particularly preferable. The above-mentioned perfluorocarbon polymer may contain an etheric oxygen atom. The ion exchange capacity of the fluorinated ion exchange resin is preferably 0.5 to 2.0 milliequivalents / g dry resin, particularly preferably 0.8 to 1.5 milliequivalents / g dry resin. The ion exchange capacity of the fluorinated ion exchange resin can be measured in the same manner as the ion exchange capacity of the ionomer.
[0074] The polymer electrolyte membrane 15 may be reinforced with a reinforcing material. Examples of the reinforcing material include a porous body, a fiber, a woven fabric, a nonwoven fabric, etc. Examples of the material for the reinforcing material include polytetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, a tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, polyethylene, polypropylene, polyphenylene sulfide, etc. In order to further improve durability, the polymer electrolyte membrane 15 may contain one or more atoms selected from the group consisting of cerium and manganese. Cerium and manganese decompose hydrogen peroxide, which is a substance that causes deterioration of the polymer electrolyte membrane 15. Cerium and manganese are preferably present in the polymer electrolyte membrane 15 as ions. The polymer electrolyte membrane 15 may contain silica, heteropolyacid (zirconium phosphate, phosphomolybdic acid, phosphotungstic acid, etc.), or the like, as a water retention agent to prevent drying.
[0075] The thickness of the polymer electrolyte membrane is preferably 10 μm to 30 μm, more preferably 15 μm to 25 μm. If the thickness of the polymer electrolyte membrane is equal to or less than the upper limit of the above range, the deterioration of the power generation performance of the solid polymer electrolyte fuel cell under low humidification conditions can be suppressed. Furthermore, if the thickness of the polymer electrolyte membrane is equal to or more than the lower limit of the above range, gas leakage and electrical short circuits can be suppressed. The thickness of the polymer electrolyte membrane is measured by observing a cross section of the polymer electrolyte membrane with a scanning electron microscope or the like.
[0076] <Method of manufacturing membrane electrode assembly> The membrane electrode assembly 10 is produced, for example, by the following method. (α) A method in which a catalyst layer 11 and a catalyst layer 21 are formed on a polymer electrolyte membrane 15 to form a membrane catalyst layer assembly, and the membrane catalyst layer assembly is sandwiched between a gas diffusion layer 12 and a gas diffusion layer 22 . (β) A method in which a catalyst layer 11 is formed on a gas diffusion layer 12 to form an anode 13 , a catalyst layer 21 is formed on a gas diffusion layer 22 to form a cathode 14 , and a polymer electrolyte membrane 15 is sandwiched between the anode 13 and the cathode 14 .
[0077] When the membrane electrode assembly 10 has a carbon layer, the membrane electrode assembly 10 is produced, for example, by the following method. (γ) A method in which a dispersion containing carbon and a nonionic fluorine-containing polymer is applied onto a base film and dried to form a carbon layer, a catalyst layer 11 is formed on the carbon layer, and a laminate in which the carbon layer and catalyst layer 21 are formed in this order on the base film by a similar method is separately prepared, the catalyst layer 11 and the polymer electrolyte membrane 15, and the catalyst layer 21 and the polymer electrolyte membrane 15 are bonded together, and each base film is peeled off to form a membrane catalyst layer assembly having a carbon layer, and the membrane catalyst layer assembly is sandwiched between a gas diffusion layer 12 and a gas diffusion layer 22. (δ) A method in which a dispersion containing carbon and a nonionic fluorine-containing polymer is applied onto the gas diffusion layer 12 and the gas diffusion layer 22, respectively, and dried to form a carbon layer, and a membrane catalyst layer assembly in which the catalyst layer 11 and the catalyst layer 21 are formed on the polymer electrolyte membrane 15 is sandwiched between the gas diffusion layer 12 having a carbon layer and the gas diffusion layer 22 having a carbon layer.
[0078] The polymer electrolyte membrane 15 can be formed, for example, by a method (casting method) in which a liquid composition containing an ion exchange resin is applied onto a substrate film or a catalyst layer (catalyst layer 11 or catalyst layer 21) and dried. When forming the polymer electrolyte membrane 15, for example, a liquid composition containing a liquid medium, a fluorine-containing polymer having sulfonic acid groups, and trivalent or tetravalent cerium ions may be used. When the liquid composition is used, it is preferable to perform a heat treatment in order to stabilize the polymer electrolyte membrane 15. The heat treatment temperature depends on the type of ion exchange resin, but is preferably 130°C to 200°C. If the heat treatment temperature is 130°C or higher, the ion exchange resin will not become excessively hydrated. If the heat treatment temperature is 200°C or lower, thermal decomposition of sulfonic acid groups is suppressed, and a decrease in the proton conductivity of the polymer electrolyte membrane 15 is suppressed. The polymer electrolyte membrane 15 may be treated with hydrogen peroxide water as necessary.
[0079] [Polymer electrolyte fuel cell] The polymer electrolyte fuel cell in this embodiment includes the above-mentioned membrane electrode assembly. A polymer electrolyte fuel cell is produced, for example, by forming a cell by sandwiching a membrane electrode assembly between two separators, and stacking a plurality of cells. The separator may be a conductive carbon plate having grooves formed therein that serve as passages for the fuel gas or the oxidizing gas containing oxygen (air, oxygen, etc.). Types of polymer electrolyte fuel cells include hydrogen / oxygen fuel cells, direct methanol fuel cells (DMFCs), etc. Methanol or an aqueous methanol solution used as fuel for DMFCs may be liquid-feed or gas-feed. EXAMPLES
[0080] The present disclosure will be described in detail below with reference to examples and reference examples, but the present disclosure is not limited to the following examples.
[0081] [Catalyst-supported carbon] As the catalyst-supporting carbon, the following catalyst-supporting carbon (1), catalyst-supporting carbon (2), and catalyst-supporting carbon (3) were prepared. Catalyst-supported carbon (1): Catalyst: platinum particles, catalyst content relative to total catalyst-supported carbon: 60 mass%, number-average particle diameter of platinum particles: 4.8 nm Catalyst-supported carbon (2): Catalyst: platinum particles, catalyst content relative to total catalyst-supported carbon: 50 mass%, number-average particle diameter of platinum particles: 3.3 nm Catalyst-supported carbon (3): Catalyst: platinum particles, catalyst content relative to total catalyst-supported carbon: 20 mass%, number-average particle diameter of platinum particles: 2.5 nm As the catalyst-supported carbon (3), a general platinum-supported carbon catalyst with a platinum support rate of 20% was used.
[0082] The characteristics of the catalyst-supported carbon (1) are as follows: Total specific surface area: 283 m 2 / g catalyst Total pore volume of specific mesopores: 0.15 cm 3 / g catalyst The ratio of the total pore volume of specific mesopores to the total pore volume of all mesopores and macropores: 28% Total macropore volume: 0.25 cm 3 / g catalyst
[0083] The characteristics of the catalyst-supported carbon (2) are as follows: Total specific surface area: 410m 2 / g catalyst Total pore volume of specific mesopores: 0.15 cm 3 / g catalyst The ratio of the total pore volume of specific mesopores to the total pore volume of all mesopores and macropores: 50% Total macropore volume: 0.25 cm3 / g catalyst
[0084] [Ionomer dispersion] As an ionomer, a polymer (H1) having a structural unit derived from TFE and the above unit (U1-11) (ion exchange capacity: 1.1 meq / g dry resin) was prepared. Polymer (H1) was dispersed in a dispersion medium of ethanol / water=6 / 4 (mass ratio) to prepare polymer (H1) dispersion (A) having a solid content concentration of 25.0 mass %.
[0085] [Preparation of coating solution for forming catalyst layer] <Coating fluid (a1)> 50.0 g of catalyst-supported carbon (1) was added to 363 g of distilled water and stirred thoroughly. 177 g of ethanol and 65 g of 2-propanol were further added and stirred thoroughly. 56.0 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 1 mm zirconia beads at a peripheral speed of 6 m / s and a residence time of 1.1 minutes, and this was used as coating liquid (a1).
[0086] <Coating liquid (a2)> 50.0 g of catalyst-supported carbon (1) was added to 389 g of distilled water and stirred thoroughly. 188 g of ethanol and 71 g of 2-propanol were further added and stirred thoroughly. 80.0 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 1 mm zirconia beads at a peripheral speed of 6 m / s and a residence time of 1.1 minutes, and this was used as coating liquid (a2).
[0087] <Coating fluid (a3)> 50.0 g of catalyst-supported carbon (1) was added to 431 g of distilled water and stirred thoroughly. 207 g of ethanol and 81 g of 2-propanol were further added and stirred thoroughly. 120 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 1 mm zirconia beads at a peripheral speed of 6 m / s and a residence time of 1.1 minutes, and this was used as coating liquid (a3).
[0088] <Coating fluid (a4)> 50.0 g of catalyst-supported carbon (1) was added to 363 g of distilled water and stirred thoroughly. 177 g of ethanol and 65 g of 2-propanol were further added and stirred thoroughly. 56.0 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 0.5 mm zirconia beads at a peripheral speed of 8 m / s and a residence time of 5.5 minutes, and this was used as coating liquid (a4).
[0089] <Coating fluid (a5)> 50.0 g of catalyst-supported carbon (1) was added to 389 g of distilled water and stirred thoroughly. 188 g of ethanol and 71 g of 2-propanol were further added and stirred thoroughly. 80.0 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 0.5 mm zirconia beads at a peripheral speed of 8 m / s and a residence time of 5.5 minutes, and this was used as coating liquid (a5).
[0090] <Coating fluid (a6)> 50.0 g of catalyst-supported carbon (1) was added to 431 g of distilled water and stirred thoroughly. 207 g of ethanol and 81 g of 2-propanol were further added and stirred thoroughly. 120 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 0.5 mm zirconia beads at a peripheral speed of 8 m / s and a residence time of 5.5 minutes, and this was used as coating liquid (a6).
[0091] <Coating fluid (a7)> 50.0 g of catalyst-supported carbon (3) was added to 357 g of distilled water and stirred thoroughly. 376 g of ethanol was further added and stirred thoroughly. 128 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 1.0 mm zirconia beads at a peripheral speed of 6 m / s and a residence time of 4.3 minutes, and this was used as coating liquid (a7).
[0092] <Coating fluid (a8)> 50.0 g of catalyst-supported carbon (2) was added to 375 g of distilled water and stirred thoroughly. 397 g of ethanol was further added and stirred thoroughly. 150 g of polymer (H1) dispersion (A) was added to this, and dispersed in a bead mill (Ashizawa Finetech LZ015) using 1.0 mm zirconia beads at a peripheral speed of 6 m / s and a residence time of 1.1 minutes, and this was used as coating liquid (a8).
[0093] [Preparation of coating solution for forming intermediate layer (carbon layer)] <Coating fluid (c1)> 21.0 g of ethanol and 24.0 g of distilled water were added to 10.0 g of vapor grown carbon fiber (manufactured by Showa Denko KK, product name: VGCF-H, average fiber diameter: about 150 nm, fiber length: 10 to 20 μm) and thoroughly stirred. 20.0 g of polymer (H1) dispersion liquid (A) was added thereto and thoroughly stirred, and further mixed and pulverized using a homogenizer to obtain coating liquid (c1).
[0094] [Formation of catalyst layer] <Example C1> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a1) was applied on top of the coated layer to a platinum content of 0.20 mg / cm2. 2 The resulting layer was coated with a die coater and dried to obtain a cathode (gc1). Note that the above "amount of platinum" refers to the amount of catalyst contained per unit area of the catalyst layer. Coating solution (a7) was applied to a gas diffusion layer substrate with a sealing layer (SGL Carbon Co., Ltd., 25BC) at a platinum amount of 0.05 mg / cm 2 The resulting mixture was applied using a die coater so that the coating became as shown in FIG.
[0095] As the polymer electrolyte membrane, a 20 μm-thick ion exchange membrane made of a perfluorocarbon polymer having sulfonic acid groups (manufactured by Asahi Glass Co., Ltd., product name: Flemion, ion exchange capacity: 1.1 meq / g dry resin) was prepared. The polymer electrolyte membrane was sandwiched between the anode (ga1) and the cathode (gc1), and the catalyst layers of the cathode (ga1) and anode (gc1) were pressed onto the polymer electrolyte membrane by hot pressing to form a membrane electrode assembly (electrode area: 25 cm 2 ) was obtained.
[0096] <Example 1> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a2) was then applied on top of the coated layer to a platinum content of 0.20 mg / cm. 2 The resulting mixture was applied with a die coater so that the thickness became equal to that of the cathode (gc2), and then dried to obtain a cathode (gc2). A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc2) was used instead of the cathode (gc1).
[0097] <Example 2> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a3) was then applied on top of the coated layer to a platinum content of 0.20 mg / cm. 2 The resulting mixture was coated with a die coater so that the thickness became equal to that of the cathode (gc3) and then dried. A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc3) was used instead of the cathode (gc1).
[0098] <Example C2> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a4) is then applied on top of the coated layer to a platinum content of 0.20 mg / cm2. 2 The resulting mixture was applied using a die coater so as to obtain a cathode (gc4). A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc4) was used instead of the cathode (gc1).
[0099] <Example 3> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a5) is then applied on top of the coated layer to a platinum content of 0.20 mg / cm. 2 The resulting mixture was applied using a die coater so as to obtain a cathode (gc5). A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc5) was used instead of the cathode (gc1).
[0100] <Example C3> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a6) was then applied on top of the coated layer to a platinum content of 0.20 mg / cm. 2 The resulting mixture was applied using a die coater so that the thickness became equal to that of the cathode (gc6), and then dried. A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc6) was used instead of the cathode (gc1).
[0101] <Example 4> Coating liquid (c1) was applied at a solid content of 3.0 mg / cm on a gas diffusion layer substrate without a filling layer (manufactured by NOK, H2315 T10X6). 2 The coating solution (a8) is then applied on top of the coated layer to a platinum content of 0.10 mg / cm. 2 The resulting mixture was applied using a die coater so as to obtain a cathode (gc7). A membrane electrode assembly was obtained in the same manner as in Example C1, except that the cathode (gc7) was used instead of the cathode (gc1).
[0102] [Measurement and Evaluation] <Ionomer content per 100 parts by mass of carbon support> The content (parts by mass) of the ionomer relative to 100 parts by mass of the carbon support in the cathodes of the above examples is shown in Table 1 ("Ionomer content" in Table 1).
[0103] <Ionomer occupancy rate> The coating liquid used to form the cathode in the above example was applied to a PET film, dried, and the coating layer was scraped off to obtain a powder that was used as a "catalyst-supported carbon sample with ionomer attached." In addition, a coating liquid that did not contain ionomer (i.e., a mixture of catalyst-supported carbon and a solvent) was applied to a PET film, dried, and the coating layer was scraped off to obtain a powder that was used as a "catalyst-supported carbon sample without ionomer attached." Using these samples, the pore distribution was determined for each sample using the method described above, and the ionomer occupancy rate (%) for each sample was calculated. The results are shown in Table 1.
[0104] <Macropore volume after ionomer deposition> From the pore distribution of the above-mentioned "catalyst-supported carbon sample with ionomer attached" in each example, the total pore volume (cm) of macropores per unit mass of the catalyst-supported carbon in the ionomer-attached state was calculated. 3 The results are shown in Table 1 ("Macropore volume" in Table 1).
[0105] <Power generation performance (1)> The membrane electrode assembly obtained in the above example was incorporated into a power generation cell, and hydrogen (utilization rate 70%) / air (utilization rate 50%) was supplied at normal pressure, the cell temperature was 80°C, and the current density was 1.0 A / cm 2 The cell voltage (V) at the beginning of operation was measured. Hydrogen with a dew point of 80°C was supplied to the anode side, and air with a dew point of 80°C was supplied to the cathode side (relative humidity in the cell: 100% RH). The results are shown in Table 1 ("100% RH cell voltage" in Table 1).
[0106] <Power generation performance (2)> The membrane electrode assembly obtained in the above example was incorporated into a power generation cell, and hydrogen (utilization rate 70%) / air (utilization rate 50%) was supplied at normal pressure, the cell temperature was 80°C, and the current density was 1.0 A / cm 2The cell voltage (V) at the beginning of operation was measured. Hydrogen with a dew point of 53°C was supplied to the anode side, and air with a dew point of 53°C was supplied to the cathode side (relative humidity in the cell: 30% RH). The results are shown in Table 1 ("30% RH cell voltage" in Table 1).
[0107] [Table 1]
[0108] As can be seen from the results shown in Table 1, in Examples 1 to 4, the amount of catalyst used was reduced while increasing the output of the fuel cell, compared to Examples C1 to C3.
[0109] The disclosure of Japanese Patent Application No. 2019-232523, filed on December 24, 2019, is incorporated herein by reference in its entirety. All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference. [Explanation of symbols]
[0110] 10 membrane electrode assembly, 11 catalyst layer, 12 gas diffusion layer, 13 anode, 14 cathode, 21 catalyst layer, 22 gas diffusion layer
Claims
1. The catalyst layer includes a catalyst-supported carbon in which a platinum-containing catalyst is supported on a carbon support, and an ionomer, The catalyst-supporting carbon has mesopores with a pore diameter of 2 nm or more and less than 10 nm in a pore distribution obtained by a nitrogen adsorption method, At least a portion of the ionomer is present in the mesopores having a pore diameter of 2 nm or more and less than 10 nm; The content of the ionomer relative to 100 parts by mass of the carbon support is 100 parts by mass or more, The ionomer occupies 50% by volume or less of the total volume of the mesopores having a pore diameter of 2 nm or more and less than 10 nm; A catalyst layer used as a cathode catalyst layer in a membrane electrode assembly for a polymer electrolyte fuel cell.
2. The catalyst-supporting carbon in the catalyst layer, with the ionomer attached thereto, has a pore distribution obtained by a nitrogen adsorption method, and has a pore diameter of 50 nm or more of 0.03 cm 3 2. The catalyst layer according to claim 1, comprising at least 1.0 g catalyst.
3. The content of the catalyst per unit area of the catalyst layer is 0.2 mg / cm 2 3. The catalyst layer according to claim 1 or 2, wherein:
4. The catalyst layer according to any one of claims 1 to 3, wherein the catalyst comprises at least one selected from the group consisting of platinum particles and platinum alloy particles.
5. The catalyst layer according to claim 4, wherein the number average particle size of the catalyst is 1 nm to 20 nm.
6. 6. The catalyst layer according to claim 1, wherein a content of the catalyst relative to the entire catalyst-supporting carbon is 10% by mass to 70% by mass.
7. an anode having a first gas diffusion layer and a first catalyst layer provided on one surface of the first gas diffusion layer; a cathode having a second gas diffusion layer and a second catalyst layer provided on one surface of the second gas diffusion layer; a polymer electrolyte membrane disposed between the first catalyst layer and the second catalyst layer; Equipped with A membrane / electrode assembly for a polymer electrolyte fuel cell, wherein at least the second catalyst layer is the catalyst layer according to any one of claims 1 to 6.
8. A polymer electrolyte fuel cell comprising the membrane electrode assembly for a polymer electrolyte fuel cell according to claim 7.
Citation Information
Patent Citations
Fuel cell
JP2002025560A
Electrocatalyst and its production method
JP2005034836A
Method of manufacturing catalyst support body for polymer electrolyte fuel cell, and polymer electrolyte fuel cell
JP2008041498A
Supported catalyst for fuel cell and fuel cell
JP2012129059A
Electrode catalyst for fuel battery
JP2017117665A